An Analysis of the Spatial Distribution of Urban Public Services in the Districts of Tabriz Metropolis, Iran - Omid Mobaraki; Ebrahim Sami (Sustainable Earth Trends)
This research aims to analyze the spatial distribution of urban public services in the metropolitan districts of Tabriz. This study is an applied research type and its method is descriptive-analytical. To analyze the data, the TOPSIS model as well as cluster analysis and SPSS and GIS software were used. The research results showed that there was no favorable spatial justice between the districts of Tabriz city in privileging public urban services. In other words, districts 2, 3, and 5 were on one level (first level), districts 6, 7, and 4 were on one level (second level) and districts 9, 8, 1, and 10 were on one level (third level). In deprived districts, nonconforming population growth with service needs, lack of green and recreational spaces, lack of suitable health-medical, commercial, and sports services, increase in population growth rate, lack of educational and cultural facilities, low employment, low-income strata and immigrants` residence, construction of unlicensed buildings and indiscriminate expansion in these districts have intensified the level of instability. Therefore, for the optimal distribution of public services between districts of Tabriz city, first of all, the approach of social justice should be placed on the agenda of the managers and decision-makers of Tabriz city so that the distribution of services and facilities between the districts of Tabriz city is balanced according to population needs.